MIXED CEMENTS BASED ON SULPHOALUMINATE-BELITE CLINKERS (Academia Science Repository, 2023)
It can be noted that mixed cements containing sulfoaluminate-belite clinkers are characterized by an intensive set of strength in the first day, which continuously increases.